SEXUAL TRAITS ARE SENSITIVE TO GENETIC STRESS AND PREDICT EXTINCTION RISK IN THE STALK‐EYED FLY, DIASEMOPSIS MEIGENII. (22nd May 2013) - Bellamy, Lawrence; Chapman, Nadine; Fowler, Kevin; Pomiankowski, Andrew
Abstract : The handicap principle predicts that sexual traits are more susceptible to inbreeding depression than nonsexual traits. However, this hypothesis has received little testing and results are inconsistent. We used 11 generations of full‐sibling mating to test the effect of inbreeding on sexual and nonsexual traits in the stalk‐eyed fly Diasemopsis meigenii . Consistent with the theoretical predictions, the male sexual trait (eyespan) decreased more than nonsexual traits (female eyespan and male wing length), even after controlling for body size variation. In addition, male eyespan was a reliable predictor of line extinction, unlike other nonsexual traits. After 11 generations, inbred lines were crossed to generate inbred and outbred families. All morphological traits were larger in outbred individuals than inbred individuals. This heterosis was greater in male eyespan than in male wing length, but not female eyespan. The elevated response in male eyespan to genetic stress mirrored the result found using environmental stress during larval development and suggests that common mechanisms underlie the patterns observed. Overall, these results support the hypothesis that male sexual traits suffer more from inbreeding depression than nonsexual traits and are in line with predictions based on the handicap principle.